1999
DOI: 10.1002/14651858.cd001855
|View full text |Cite
|
Sign up to set email alerts
|

Helmets for preventing head and facial injuries in bicyclists

Abstract: Helmets for preventing head and facial injuries in bicyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
347
4
24

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(384 citation statements)
references
References 35 publications
9
347
4
24
Order By: Relevance
“…13 This same risk-compensation behaviour has been observed in (non-sport) cyclists 14 , which is again relevant since cycle helmets cannot completely eliminate the risk of head or brain injuries. 15 We are not arguing against the benefit of sport, but rather that its footprint needs to consider the negative as well as positive effects on cognition.…”
Section: Cognitive Footprint Of Sportmentioning
confidence: 99%
“…13 This same risk-compensation behaviour has been observed in (non-sport) cyclists 14 , which is again relevant since cycle helmets cannot completely eliminate the risk of head or brain injuries. 15 We are not arguing against the benefit of sport, but rather that its footprint needs to consider the negative as well as positive effects on cognition.…”
Section: Cognitive Footprint Of Sportmentioning
confidence: 99%
“…These studies demonstrated a "large protective effect of helmets" that supported a causal mechanism and could not be explained by selection bias, observation bias, confounding or chance. Helmets conferred a 63% to 88% reduction in the risk of head and brain injury for all ages, a 65% reduction of injuries to upper and mid-facial areas, a 69% protection from crashes involving motor vehicles and a 68% protection from all other causes (13). The second meta-analysis included cross-sectional surveys of injured and noninjured cyclists in addition to case-control studies (14).…”
Section: Understanding the Effectiveness And Limitations Of Bicycle Hmentioning
confidence: 99%
“…The second meta-analysis included cross-sectional surveys of injured and noninjured cyclists in addition to case-control studies (14). It presented overall odds ratios (ORs) for head and brain injuries similar to those of the Cochrane review (13) and also had sufficient data to calculate an OR for fatalities. Based on four deaths among 2461 helmeted cyclists and 43 deaths among 4794 non-helmeted cyclists, the OR was 0.27 (eg, a 73% reduction) with a 95% CI of 0.10 to 0.71.…”
Section: Understanding the Effectiveness And Limitations Of Bicycle Hmentioning
confidence: 99%
“…Perhaps the knowledge gap is related to efficacy of helmet use in adults -yet a Cochrane review demonstrated that helmets reduce the risk of head, brain, and severe brain injury for all cycling ages by 63% to 88%. 6 Perhaps they believe that, as adult, regular cyclists (or rare cyclists), they are exempt from harm. Relaying your experience treating cyclists in the trauma room may help patients re-evaluate their vulnerability.…”
mentioning
confidence: 99%